Incidence of acute kidney injury in asphyxiated babies in university of Uyo teaching hospital, Uyo, Nigeria - Emmanuel, Ikpeme Enobong; Tony, Dixonumo Ofonime; Paulinus, Udoh Mary; J., Udo Jacob (International Journal of Research in Medical Sciences, 2020)
Background: Acute Kidney Injury (AKI) is a consequence of birth asphyxia. In resource poor countries like ours, birth asphyxia still contributes to the high rates of neonatal morbidity and mortality. A few studies have reported the incidence of AKI in birth asphyxia in Nigeria but none from Uyo, south-south region of Nigeria. Methods: A descriptive cross sectional study carried out in the Newborn Unit of the University of Uyo Teaching hospital, Uyo, Nigeria over a period of eight months. One hundred and four term neonates with provisional diagnosis of birth asphyxia using Apgar scoring were recruited. Blood sample was collected within six hours of life from each subject for serum creatinine estimation using modified Jaffe method. Urine output was assessed by application of plastic collection bag to the skin by adhesive patch. AKI was diagnosed when sCr >1.5mg/dl while oliguria was defined as urinary output <1.5ml/kg/hour. Results: Of the total of 104 asphyxiated neonates enrolled into the study, 56 (53.8%) were males while 48 (46.2%) were females giving a male/female ratio of 1.2:1. Twenty-eight (26.9%) of the subjects had severe birth asphyxia; 52 (50%) had moderate birth asphyxia while 24 (23.1%) were mildly asphyxiated. Incidence of AKI was 48 (46.1%), twelve (11.5%) had AKI based on serum creatinine criteria while 36 (34.6%) had AKI based on urinary output criteria. The mean urinary output (ml/kg/hr) for the subjects was 1.65±0.68 while the mean serum creatinine (mg/dl) was 0.88±0.46. Conclusions: The incidence of AKI among asphyxiated neonates in our locale is high at 46.1%.